Efficacy of Zero-Profile Implant in Anterior Fusion to Treat Degenerative Cervical Spine Disease: Comparison with Techniques Using Bone Graft and Anterior Plating - Chang, Han; Baek, Dong-Hoon; Choi, Byung-Wan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background The efficacy of anterior fusion using zero-profile implant (Zero-P) in the surgical treatment of degenerative cervical disease was investigated through radiographic and clinical comparisons with existing treatments using autograft or allograft and anterior plating.Material and Methods A total of 130 patients who underwent anterior decompression and fusion for degenerative cervical spine disease with a follow-up of at least 1 year were analyzed retrospectively. The cases were divided into three groups: autograft and plate (38 cases, group A), allograft and plate (44 cases, group B), and Zero-P (48 cases, group C). Maintenance of lordosis, extent of subsidence, and fusion were evaluated radiologically and compared among preoperative, postoperative, and final follow-up time points. In addition, changes in Visual Analog Scale (VAS) and Neurologic Disability Index (NDI) scores and the presence of complications were evaluated for clinical analysis.Results Operation time was significantly less in group C (p = 0.007, 0.002). Maintenance of entire and segmental lordosis after surgery was better in groups A and B compared with group C (p = 0.002, 0.001); however, the extent of loss of lordosis from the surgery to the final follow-up did not show any significant differences. Regarding the extent of subsidence, the increase of height between the vertebral bodies after the surgery was 3.10, 2.89, and 2.68 mm in group A, group B, and group C, respectively (p = 0.14), and changed to − 1.27, − 2.41, and − 1.2 mm at the final follow-up (p = 0.012). VAS and NDI scores were improved from 7.2 to 3 and 34 to 12, respectively, but there were no significant differences. Nonunion occurred in two cases in both group B and group C. In terms of clinical complications, two cases of persistent donor site pain were found in group A; one case of persistent dysphagia was found in both group A and group B.Conclusion Anterior cervical fusion using Zero-P has a shorter operation time and less subsidence compared with conventional surgical techniques. Thus it can be considered a useful technique for the surgical treatment of degenerative cervical disease.
Keywords: cervical spine; ACDF; zero-profile implant